A new species of the genus Rhipidandrus LeConte, 1862 from China, with description of the immature stages (Coleoptera: Tenebrionidae: Bolitophagini) - Zhang, Heng; Ye, Yingying; Wang, Mengyue; Wei, Zhaoming (Zootaxa, 2025)
Rhipidandrus LeConte, 1862 is a small genus of mycophagous beetles. Previously, only one species, Rhipidandrus speculifrons (Gebien, 1922), was known to occur in China. Here, we report the discovery of a new species, Rhipidandrus longipunctatus Zhang sp. nov., from the Qinling Mountains, Shaanxi. This new species is distinguished from all congeners by the presence of longitudinal punctures on the pronotum. Detailed morphological descriptions of the adult, larva, pupa, and egg are provided. Additionally, a key to the two known Chinese species of Rhipidandrus is included.